A low carbohydrate-protein supplement improves endurance performance in female athletes - McCleave, E. L.; Ferguson-Stegall, L.; Ding, Z.; Doerner, P. G.; Wang, B.; Lynne, M.; Ivy, J. L. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to investigate if a low mixed carbohydrate (CHO) plus moderate protein (PRO) supplement, provided during endurance exercise, would improve time to exhaustion (TTE) in comparison to a traditional 6% CHO supplement. Fourteen (n = 14) trained female cyclists and triathletes cycled on 2 separate occasions for 3 hours at intensities varying between 45 and 70% VO2max, followed by a ride to exhaustion at an intensity approximating the individual's ventilatory threshold average 75.06% VO2max. Supplements (275 mL) were provided every 20 minutes during exercise and were composed of a CHO mixture (1% each of dextrose, fructose, and maltodextrin) + 1.2% PRO (CHO + PRO) or 6% dextrose only (CHO). The TTE was significantly greater with CHO + PRO in comparison to with CHO (49.94 ± 7.01 vs. 42.36 ± 6.21 minutes, respectively, p < 0.05). Blood glucose was significantly lower during the CHO + PRO trial (4.07 ± 0.12 mmol·L-1) compared to during the CHO trial (4.47 ± 0.12 mmol·L-1), with treatment × time interactions occurring from 118 minutes of exercise until exhaustion (p < 0.05). Results from the present study suggest that the addition of a moderate amount of PRO to a low mixed CHO supplement improves endurance performance in women above that of a traditional 6% CHO supplement. Improvement in performance occurred despite CHO + PRO containing a lower CHO and caloric content. It is likely that the greater performance seen with CHO + PRO was a result of the CHO-PRO combination and the use of a mixture of CHO sources.